2022
DOI: 10.1186/s12864-022-08773-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DNA methylation in porcine immune cells reveals novel regulatory elements associated with cell-specific gene expression and immune capacity traits

Abstract: Background Genetics studies in the porcine immune system have enhanced selection practices for disease resistance phenotypes and increased the efficacy of porcine models in biomedical research; however limited functional annotation of the porcine immunome has hindered progress on both fronts. Among epigenetic mechanisms that regulate gene expression, DNA methylation is the most ubiquitous modification made to the DNA molecule and influences transcription factor binding as well as gene and pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Lowly methylated regions (LMRs) were highly enriched among neutrophil SEGs ( p = 2.4 × 10 -3 ). In total, 119 neutrophil SEGs showed LMRs in comparison with other porcine immune cell methylomes reported previously ( Supplementary File S6 ) ( Corbett et al, 2022 ). LMRs across SEGs gene features showed that promoters and transcription termination sires (TTS) have higher enrichment with the expression of SEGs ( Figure 6B ).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Lowly methylated regions (LMRs) were highly enriched among neutrophil SEGs ( p = 2.4 × 10 -3 ). In total, 119 neutrophil SEGs showed LMRs in comparison with other porcine immune cell methylomes reported previously ( Supplementary File S6 ) ( Corbett et al, 2022 ). LMRs across SEGs gene features showed that promoters and transcription termination sires (TTS) have higher enrichment with the expression of SEGs ( Figure 6B ).…”
Section: Resultsmentioning
confidence: 56%
“…We used published DNA methylation data generated from samples collected from the same pigs in parallel ( Corbett et al, 2022 ) to determine whether neutrophil DNA methylation was related to gene expression and accessible chromatin regions. Also, we tested the significant enrichment between differentially methylated regions (DMR) (calculated across the same immune cell populations used in this study) and SEGs and HEGs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three‐color flow cytometry analyses were performed to distinguish CD4+ and CD8+ T cell subpopulations at the Medical Laboratory Animal Center (Hubei Medical College, China). Briefly, peripheral blood mononuclear cells were labeled with biotin‐labeled anti‐porcine CD3 ε , and the CD3 ε ‐positive fraction was further separated into CD4+ T cell subsets (CD4+; CD3 ε + CD8 α − CD4+) and CD8+ T cell subsets (CD8+; CD3 ε + CD8 α + CD4−) (Corbett et al, 2022). The monoclonal antibodies CD3‐SprD (PE‐CY5), anti‐piglet CD8‐PE and anti‐piglet CD4‐FITC were purchased from Southern Biotech.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was isolated using PureLink Genomic DNA kit (Invitrogen), and quality and quantity were assessed on a Qubit fluorometer (Invitrogen). WGBS was performed at the Michigan State University (MSU) Research Technology Support Facility (RTSF) Genomics Core using methods previously reported by our group (Corbett et al 2022). Briefly, DNA samples were spiked with unmethylated lambda phage DNA (5 ng lambda DNA/1 μg sample DNA) to assess bisulfite conversion rates.…”
Section: Sample Collection and Nucleic Acid Isolationmentioning
confidence: 99%